Birth prevalence of achondroplasia: A systematic literature review and meta‐analysis. Issue 10 (17th August 2020) - Foreman, Pamela K.; van Kessel, Femke; van Hoorn, Rosa; van den Bosch, Judith; Shediac, Renée; Landis, Sarah
Abstract: Achondroplasia is a genetic disorder that results in disproportionate short stature. The true prevalence of achondroplasia is unknown as estimates vary widely. This systematic literature review and meta‐analysis was conducted to better estimate worldwide achondroplasia birth prevalence. PubMed, Embase, Scielo, and Google Scholar were searched, complemented by manual searching, for peer‐reviewed articles published between 1950 and 2019. Eligible articles were identified by two independent researchers using predefined selection criteria. Birth prevalence estimates were extracted for analysis, and the quality of evidence was assessed. A meta‐analysis using a quality effects approach based on the inverse variance fixed effect model was conducted. The search identified 955 unique articles, of which 52 were eligible and included. Based on the meta‐analysis, the worldwide birth prevalence of achondroplasia was estimated to be 4.6 per 100, 000. Substantial regional variation was observed with a considerably higher birth prevalence reported in North Africa and the Middle East compared to other regions, particularly Europe and the Americas. Higher birth prevalence was also reported in specialized care settings. Significant heterogeneity (Higgins I 2 of 84.3) was present and some indication of publication bias was detected, based on visual asymmetry of the Doi plot with a Furuya‐Kanamori index of 2.73. Analysis of pooled data from the current literature yields a worldwide achondroplasia birth prevalence of approximately 4.6 per 100, 000, with considerable regional variation. Careful interpretation of these findings is advised as included studies are of broadly varying methodological quality.